Local Regulation on Inclusive Education: Assessing Educational Policy Commitment and Affects of Yogyakarta Local Government Indonesia - Santosa, Sedya; Kamala, Izzatin (UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to analyze the implementation of the Governor Regulation of the Special Region of Yogyakarta Number 77 of 2022 concerning the Implementation of Inclusive Education, with a focus on access for Children with Special Needs (ABK), the existence of Disability Service Units (ULD), the availability of Special Education Support Teachers (GPK), and accessible facilities and infrastructure. Although this regulation is progressive and aims for comprehensive integration, several studies evaluating it using the Inclusion Index in public elementary schools yielded achievement scores of around 76%. These findings indicate a gap of nearly 24% from the ideal inclusion standard that suggsets although formal policies exist, their implementation is not optimal. The method used is a legal-normative approach with a descriptive qualitative approach through document analysis, regulations, media reports, and official publications up to the end of 2024. Analysis using Edward's policy implementation theory indicates that the clarity of communication greatly influences the policy's effectiveness, the structure's readiness, and the implementers' attitude. The findings reveal that there is still a gap between norms and reality in all four aspects. Thousands of children with special needs are not enrolled in school, which challenges communication and policy structure. The ULD is only active in some areas, indicating that the bureaucratic structure is not optimal. The number of GPK is still limited and unevenly distributed, reflecting resource constraints. Accessible facilities are not widely available, posing a real barrier to inclusion. However, there has been progressing, such as regular teacher training and support in certain areas.